The Southeast Asian economic miracle / Young C Kim - Young, Kim, edited by
There is widespread agreement that the world's most successful developing countries in the 1980s were those in Southeast Asia. Following in the footsteps of postwar Japan and more recently Korea, the populations of Thailand, Malaysia, Indonesia, Singapore, Hong Kong, and the Philippines have made enormous strides in income, industrial and agricultural production, exports, education, health, nutrition, consumption, and other development indicators. This book brings together political scientists, economists, officials of Asian governments, the United States, and representatives of the multilateral banks to analyze and explain Southeast Asia's extraordinary growth.